Developing an integrated teaching factory model for enhancing industry-standard competencies in vocational education: a systematic literature review - Setia Budi Wibowo; Nining Latianingsih; Satria Evans Umboh; Amroh Umaemah; Ulfah Irani Z. (Jurnal Konseling dan Pendidikan, 2025)
Vocational education plays a crucial role in preparing a skilled workforce capable of responding to rapid industrial transformation in the digital manufacturing era. Despite various reforms, a persistent mismatch between vocational graduates’ competencies and industry requirements remains a structural challenge. This study aims to develop an Integrated Teaching Factory (ITF) framework as a conceptual model to strengthen industry-standard competencies in vocational education. The study employs a qualitative approach using a PRISMA-guided systematic literature review of national and international publications published between 2015 and 2025. Relevant studies were identified, screened, and analyzed through thematic content analysis to extract recurring patterns related to production-based learning, digital manufacturing integration, and cross-sector collaboration. The synthesis reveals three interdependent dimensions that underpin effective Teaching Factory implementation: industry-aligned competency mapping, digital production integration, and collaborative governance structures involving vocational institutions, industry partners, and public stakeholders. These dimensions are integrated into a coherent framework explaining how vocational education can systematically align curriculum design, technological infrastructure, and partnership governance in digitally intensive manufacturing contexts. The study contributes theoretically by integrating Public–Private Partnership theory, Stakeholder theory, and the Triple Helix model, and practically by providing strategic guidance for policymakers and practitioners in designing sustainable and scalable vocational education transformation initiatives.